2021
DOI: 10.1111/micc.12703
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRPV4 channel in vasodilation and neovascularization

Abstract: The transient receptor potential vanilloid type 4 (TRPV4) channel, a Ca2+‐permeable nonselective cation channel, is widely distributed in the circulatory system, particularly in vascular endothelial cells (ECs) and smooth muscle cells (SMCs). The TRPV4 channel is activated by various endogenous and exogenous stimuli, including shear stress, low intravascular pressure, and arachidonic acid. TRPV4 has a role in mediating vascular tone and arterial blood pressure. The activation of the TRPV4 channel induces Ca2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 122 publications
(357 reference statements)
0
10
1
Order By: Relevance
“…Vessel maturation after hindlimb ischaemia is a complex process that is orchestrated by several cell types, including endothelial cells, perivascular cells like pericytes, VSMCs and macrophages. In the present study, we could not find any effect of TRPC6 deficiency on angiogenesis determined by the number of CD31 positive capillaries reportedly involved in EDH (Chen & Li, 2021;Félétou, 2016;Liu et al, 2021;Naik & Walker, 2018), play critical roles in angiogenesis and arteriogenesis after hindlimb ischaemia (Troidl et al, 2010(Troidl et al, , 2009Yamada et al, 2021). Thus, the hyperpolarization of VSMCs is likely to be a common and important step for vessel maturation.…”
Section: Pharmacological Inhibition Of Trpc6 Facilitates Blood Flow R...contrasting
confidence: 51%
“…Vessel maturation after hindlimb ischaemia is a complex process that is orchestrated by several cell types, including endothelial cells, perivascular cells like pericytes, VSMCs and macrophages. In the present study, we could not find any effect of TRPC6 deficiency on angiogenesis determined by the number of CD31 positive capillaries reportedly involved in EDH (Chen & Li, 2021;Félétou, 2016;Liu et al, 2021;Naik & Walker, 2018), play critical roles in angiogenesis and arteriogenesis after hindlimb ischaemia (Troidl et al, 2010(Troidl et al, , 2009Yamada et al, 2021). Thus, the hyperpolarization of VSMCs is likely to be a common and important step for vessel maturation.…”
Section: Pharmacological Inhibition Of Trpc6 Facilitates Blood Flow R...contrasting
confidence: 51%
“…On the other hand, Ca 2+ is a promoter of the endothelial-derived hyperpolarisation pathway in ECs that stimulates the opening of the small and intermediate conductance Ca 2+ -sensitive K + channels (K Ca )-SK Ca (K Ca 2.3) and IK Ca (K Ca 3.1), leading to the hyperpolarisation of the membrane of vascular smooth muscle cells and consequent vascular relaxation. 8 In this study, although the flap blood flow markedly increased, the increase in blood flow between the Day 5 group and the Day 7 group was not significantly different. Similarly, TRPV4 and TRPV1 expression on Days 5 and 7 was significantly down-regulated compared with that on Day 3.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al 7 reported that blood flow, vascular diameters, and microvascular count are clearly increased after flap elevation, and vascular changes are closely associated with the shear stress caused by the increased blood perfusion after surgery. Previous studies indicated that shear stress can activate some mechanosensors situated on the endothelial cell (EC) membrane to trigger several acute signalling pathways, including the synthesis of nitric oxide (NO) by endothelial NO synthase (eNOS) or release of endothelial‐derived hyperpolarisation factor, ultimately increasing the vasodilation 8,9 . In addition, during sprouting angiogenesis, the blood flow actuates the formation of the lumen through causing spherical deformations of the apical membrane of the ECs 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angioplasty and surgical bypass are considered effective revascularization methods in most patients; however, stimulating the development of an effective collateral circulation has improved myocardial cell activity and prognosis in patients with severe CHD (16,17). The ECs are activated during collateral artery formation (arteriogenesis) (18), resulting in their proliferation, migration, and differentiation into tubular structures. The surrounding tissues wrap around the ECs to form vascular walls, and vascular networks coincide, initiating the collateral circulation (19)(20)(21).…”
Section: Mir-195-3p Inhibitor Rescued the Apoptosis Of Hypoxia Injure...mentioning
confidence: 99%